PERBANDINGAN PENGGUNAAN METODE PROBLEM BASED LEARNING (PBL), METODE PROBLEM SOLVING DAN METODE STUDENTS TEAMS ACHIEVEMENT DIVISION (STAD) DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF SISWA - Rahmat, Pupu Saeful (Equilibrium: Jurnal Penelitian Pendidikan dan Ekonomi, 2021)
ABSTRACT The purpose of this study was to obtain findings about the differences in the improvement of students’ creative thinking skills between classes using problem-based learning methods, classes using problem-solving methods and classes using STAD learning methods. The research subjects were Class XI students of SMKN 1 Kadipaten in the 2018-2019 academic year. The method used in this study is a quasi-experimental. The analysis is used by using Counterbalanced Design with three classes, all of which are experimental classes. The results showed that: First, there were differences in the creative thinking abilities of students in the class using the PBL learning method and the creative thinking abilities of students in the class that used the Problem Solving learning method. where the creative thinking ability of students in a class that uses the PBL learning method is superior to the creative thinking ability of students in a class that uses the Problem Solving learning method. Second, there is no significant difference in the creative thinking ability of students in the class that uses the Problem Solving learning method with the creative thinking ability of students in classes using the STAD learning method. The creative thinking ability of students in a class that uses the Problem Solving learning method has almost the same results compared to the creative thinking ability of students in a class that uses the STAD learning method. Third, there are differences in students’ creative thinking abilities in a class that uses the PBL learning method and the creative thinking ability of students in a class that uses the STAD learning method. This shows that the use of the PBL learning method is more effective in improving students’ creative thinking skills compared to the STAD learning method. Keywords: creative thinking; STAD method; PBL method; and problem solving.